A rheumatoid arthritis patient with delivery who started certolizumab pegol and tacrolimus during pregnancy. Issue 1 (11th August 2021) - Ito, Satoshi; Ishikawa, Hajime; Kato, Ryuta
ABSTRACT: We experienced a patient in her 30s with rheumatoid arthritis (RA) who achieved delivery with the use of certolizumab pegol (CZP) and tacrolimus (TAC) during pregnancy. She developed RA in X  - 3 year and was treated with salazosulfapyridine (SASP). In X  - 2 year, she became pregnant and discontinued SASP and had a normal delivery despite joint pain during pregnancy. She restarted SASP in X  - 1 year and became pregnant again in X  year. She experienced a flare-up of RA and was referred to our rheumatic centre. We introduced CZP and TAC, and she discontinued these agents and started prednisolone just before delivery. There is reportedly minimal placental transfer of CZP because of its Fc-free structure, since the Fc part of CZP is replaced by polyethylene glycol. TAC was contraindicated during pregnancy until 2018, but its usage in such patients is now approved. Despite the flare-up of RA during pregnancy, we were able to reduce the disease activity by introducing CZP and TAC during pregnancy. We believe that the present findings support the efficacy of this approach for treating RA flare during pregnancy.